PENGARUH LINGKUNGAN KERJA FISIK, PROMOSI JABATAN DAN KOMPENSASI TERHADAP KEPUASAN KERJA - Apriawan Suamba, I Made Agus; Sariyathi, Ni Ketut (E-Jurnal Manajemen, 2015)
Human resources is key to the success of an enterprise. Companies must pay attention to the promotion process, because then compensating employees who have high initiative in obligate job will be compelled to carry out the work with the best. Compensation to employees should be fair according to the results of work of employees, especially in the provision of incentives for the provision of fair compensation and better then the employee will be motivated. This study took place at the Melia Benoa Hotel with a respondents es as 72 peoples . The data analysis technique used is multiple linear regression analysis. Based on the results of data analysis known physical work environment, promotion and compensation, and simultaneously have a significant effect on employee job satisfaction partially Melia Benoa Hotel and also note that the variable compensation as a dominant variable on employee job satisfaction Melia Benoa Hotel.
Keywords: environment, promotion, compensation